Characteristics of Chemical Solutes and Mineral Dust in Ice of the Ablation Area of a Glacier in Tien Shan Mountains, Central Asia - Chen, Yunjie; Takeuchi, Nozomu; Wang, Feiteng; Li, Zhongqin (Frontiers in Earth Science, 2022)
Diverse microbial communities live on glacial surfaces, with abundances and diversities dictated by the chemical and physical conditions of the supraglacial environment. Chemical solutes and mineral dust on glacial surfaces are generally derived from the atmosphere as aerosols, but they can also be supplied from glacial ice. In this study, a 56-m ice core from the ablation area of a mountain glacier in the Tien Shan Mountains of Central Asia was analyzed to characterize the chemical solutes and mineral dust in glacial ice. Soluble chemical ion and mineral dust analysis in the ice core showed that their concentrations varied with depth. The most dominant ion was Ca²⁺ (mean: 79.8 μEq L⁻¹), followed by Cl⁻, SO₄²⁻, NH₄⁺, and NO₃⁻. The mean dust concentration in the glacial ice was 2.5 ×105 number ml-1. Chemical solute and mineral dust concentrations in the samples indicate that melting glacial ice could potentially affect supraglacial conditions. The annual fluxes of the major ions outcropping from glacial ice were estimated based on their concentrations and the observed melt rate of the ice surface. Consequently, they were comparable to or higher than those from the atmosphere. The mean mass flux of mineral dust from glacial ice was greater than that from the atmosphere. Our results showed that glacial ice supplies chemical solutes and mineral dust to the supraglacial environment and that changing melting rates of glacial ice would affect the chemical conditions on the glacier surface and the growth of photoautotrophs on the ablating ice surface.